Implementation of Religious Habituation to Build Students' Character At Al Azhar High School Gandusari – Trenggalek - Fua’adah, Alfi (International Journal of Business, Law, and Education, 2024)
The aim of this study is to explain the practice of Duha prayer among students from the 7th to the 9th grade. The role of teachers in the use of Dhuha prayer. This type of research is qualitative research. Compiled from interviews and audio recordings. The results of this study show that teachers' behaviours in improving students' behaviours by reciting Dhuha prayer and Tahlil is expedient, that is, in accordance with the school's plan. Teachers are tutors, activity buddies, mentors, role models, activity creators, and problem solvers. The problem with following this event is that many students are late and therefore do not follow the schedule